2019
DOI: 10.5935/0103-507x.20190018
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen delivery, carbon dioxide removal, energy transfer to lungs and pulmonary hypertension behavior during venous-venous extracorporeal membrane oxygenation support: a mathematical modeling approach

Abstract: Objective To describe (1) the energy transfer from the ventilator to the lungs, (2) the match between venous-venous extracorporeal membrane oxygenation (ECMO) oxygen transfer and patient oxygen consumption (VO 2 ), (3) carbon dioxide removal with ECMO, and (4) the potential effect of systemic venous oxygenation on pulmonary artery pressure. Methods Mathematical modeling approach with hypothetical scenarios using computer simulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…HPV is maximal when mixed venous oxygen saturation (SvO 2 ) is normal and is decreased by either high or low SvO 2 [ 7 ]. The large elevation of SvO 2 during VV ECMO has been reported to potentially relieve HPV, reducing pulmonary pressure [ 8 ]. More importantly, hypercapnia is known to induce vasoconstriction of PA. Morimont et al [ 9 ] showed that veno-venous extracorporeal CO 2 removal reduced pulmonary vascular constriction related to hypercapnic acidosis and improved the pulmonary haemodynamics in a porcine acute respiratory distress syndrome model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV is maximal when mixed venous oxygen saturation (SvO 2 ) is normal and is decreased by either high or low SvO 2 [ 7 ]. The large elevation of SvO 2 during VV ECMO has been reported to potentially relieve HPV, reducing pulmonary pressure [ 8 ]. More importantly, hypercapnia is known to induce vasoconstriction of PA. Morimont et al [ 9 ] showed that veno-venous extracorporeal CO 2 removal reduced pulmonary vascular constriction related to hypercapnic acidosis and improved the pulmonary haemodynamics in a porcine acute respiratory distress syndrome model.…”
Section: Discussionmentioning
confidence: 99%
“…HPV is maximal when the mixed venous oxygen saturation (SvO 2 ) is normal and is decreased by either high or low SvO 2 [ 7 ]. A significant elevation of SvO 2 during VV ECMO was reported to potentially relieve HPV, reducing pulmonary pressure [ 8 ]. In addition, Morimont et al [ 9 ] reported that VV extracorporeal CO 2 removal ameliorated pulmonary hypertension (PH) and improved the right ventricular function in a porcine acute respiratory distress syndrome model.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described a multicompartmental mathematical model. ( 18 ) The background of oxygenation modeling was high-rated flow oxygenators. The rated flow of an oxygenator is defined by the amount of hypoxemic blood (oxygen saturation < 75%) that can be nearly fully saturated (95 - 100%) per minute.…”
Section: Methodsmentioning
confidence: 99%
“…( 5 ) We used a previously described mathematical marginal multicompartmental model of systemic SatO 2 during femoro-jugular VV-ECMO support. ( 6 ) This model accounts for recirculation proportional to ECMO blood flow and systemic, native lung and artificial lung compartments. To assess the effect of Hb level on systemic SatO 2 , we contrasted different scenarios related to patient and ECMO variables, such as systemic VO 2 rates, ECMO blood flow and CO, to highlight the dynamic care required by such patients.…”
Section: To the Editormentioning
confidence: 99%